The telomeric valine–arginine dipeptide repeat protein changes state to diffuse staining in mitosis and represses in vitro translation - Taghreed Al-Turki; Venkata Mantri; Smaranda Willcox; C. Allie Mills; Laura E. Herring; Su-Ji Cho; Hannah Lee; Caliyn Meyer; E. S. Anton; Jack D. Griffith (Proceedings of the National Academy of Sciences, 2025)
Translation of mammalian G-rich telomeric RNA via the Repeat Associated non-AUG (AUG, the mRNA start codon) mechanism can produce proteins consisting of long repeats of valine–arginine (VR) or glycine–leucine (GL) dipeptides. Their role in the cell has not been elucidated. Using confocal laser scanning microscopy combined with antibody staining we previously observed VR sequestered in punctate bodies and liquid droplets in the cytoplasm and nuclei of nonmitotic cells. Here, we report that cells in mitosis show diffuse VR staining throughout the cell, giving these cells a bright appearance. Upon mitotic enrichment using the cyclin-dependent kinase 1 (CDK1) inhibitor RO-3306. RO-3306, 100% of the mitotic cells showed the same diffuse staining. Antibody staining showed colocalization of VR and the L4 ribosomal protein in mitotic cells and in an in vitro firefly luciferase assay, VR depressed translation. Affinity purification combined with mass spectrometry identified ribosomal proteins as the major class of VR interacting proteins in U2OS cells including L4 along with tubulin and proteins related to neural degenerative diseases. This change from a sequestered, punctate state in interphase to dispersed diffuse staining in mitosis, and the affinity of VR for the L4 protein which lines the ribosomal exit tunnel suggests that an oligomerization change of VR may facilitate its involvement in inhibiting of global translation during mitosis. Extension to mouse embryonic cerebral cortical development showed clear staining in the ventricular zone where neural progenitor cells with a high mitotic index proliferate and in the cortical plate where new neurons settle.